Pengaruh Ukuran Perusahaan, Penerapan Good Corporate Governance, dan Pengungkapan Corporate Social Responsibility pada Nilai Perusahaan - Pradana, Rivandi; Astika, Ida Bagus Putra (E-Jurnal Akuntansi; Vol 28 No 3 (2019), 2019)
A company when it is established has a goal to be achieved. To achieve this goal a positive response from various parties is needed. This positive response tends to get the company to have good corporate value. To find out how the influence of company size, the application of GCG and disclosure of CSR on company value are the objectives of this study. All companies listed on the IDX during the 2013-2016 period and included in the manufacturing company sector are the population of the study. Samples obtained after using purposive sampling method were as many as 41 samples. Multiple linear regression is the analytical technique used. From the results of this study it can be concluded that the variable size of the company and the application of GCG have a positive effect on firm value, while for disclosure of CSR does not affect the value of the company. Keywords : Corporate Value, Company Size, Corporate Governance Perception Index, Corporate Social Responsibility, Indonesia Stock Exchange.